Tanggung Jawab Sosial Perusahaan untuk Pengembangan Masyarakat: Implementasi Strategi Hubungan Masyarakat PT Kereta Api Indonesia Divisi Regional III, Palembang. - Hamzah, Hamzah; Kurniawan, Iman; Santoso, Budi (Jurnal Publisitas, 2025)
This study seeks to examine the public relations strategies employed by PT Kereta Api Indonesia Regional Division III in the implementation of corporate social responsibility (CSR) programs aimed at fostering community empowerment in Palembang City, South Sumatra. Adopting a qualitative methodology with a case study approach, the research focuses on the procedural execution of the CSR initiatives, which encompasses four critical stages: problem definition, planning and programming, execution and communication, and program evaluation. The findings indicate that PT Kereta Api Indonesia Regional Division III endeavors to adhere to the prescribed stages sequentially. However, the study identifies notable challenges, including insufficient socialization during the program's implementation phase and a lack of follow-up on evaluation outcomes, which may hinder the program's overall effectiveness.